Land use changes in the rural-urban fringe: An Israeli case study - Bittner, Christian; Sofer, Michael (Land Use Policy, 2013)
The paper analyses the changing pattern of land uses in rural settlements located in the rural-urban fringe and makes a link between the results to socio-economic developments and to changes in the rural policy at the national level. Using historical sequences of land use maps and using geostatistical analysis, we observe changing land use patterns in three Moshav type settlements - the most common type of rural settlement in Israel - in three different rural-urban fringes belts along the coastal area. We identify basic trends of specialisation and intensification of agricultural land use as well as expansion of built up structures for residential and commercial purposes. These trends which are rather similar for all three cases, we argue, reflect economic and social changes in rural settlements in general and in the rural-urban fringe in particular. The evolving patterns in the three Moshavim in the Israeli rural-urban fringe (RUF) can be understood as adjustment measures at the household level to development and changing policies at the macro level, particularly towards the rural sector. There are two major domains of change. First, a transition from dependence on farming to a more diversified economic base suggesting newly shaped interrelationships with the urban space. Second, a new residential development program which has rejuvenated failing and ageing rural settlements. The outcome is a major process of restructuring which affects the economic, social and environmental spheres, and necessitates sensitivity on the part of institutional decision makers towards the complex and diverse realities of relevant actors on the ground, through which all current and future land use policies are mediated. Moreover, being exposed to uncontrolled and often chaotic adjustment measures over the last three decades, it might be necessary to regulate and preserve some of the Moshav's distinct features so it does not to fade into an 'ordinary suburb'. © 2012 Elsevier Ltd.
UnivIS-Import:2015-04-20:Pub.2013.nat.dgeo.IG.zentr.landus
Keywords: Israel; Land use; Moshav; Rural-urban fringe